Pengaruh Pelatihan, Motivasi Dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada Rsud Waluyo Jati Kraksaan Kabupaten Probolinggo - Agustina Pujiastutik; Fitri Imanullahir (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted at Waluyo Jati Kraksaan Hospital Probolinggo District with the aim to determine the effect of Training, Motivation and Job Satisfaction on Employee Performance at Waluyo Hospital Jati Kraksaan Probolinggo District. This study uses a quantitative approach with the type of research used is associative. Data collection methods with interviews, observation, questionnaires and documentation, the sample used was 60 respondents including medical and non-medical employees. Data analysis method in the form of multiple linear regression analysis, using the help of SPSS 26 for Windows program. The results showed that (1) simultaneous training, motivation and job satisfaction had a significant effect on the performance of Waluyo Jati Kraksaan Hospital, Probolinggo District, (2) partially the training, motivation and job satisfaction had a significant effect on performance of Waluyo Jati Kraksaan Hospital Probolinggo District(3) Training Variables that have a dominant influence on performance at Waluyo Hospital Jati Kraksaan Probolinggo Regency.